Pengaruh Indeks Pembangunan Manusia (IPM) dan Pendidikan Terhadap Kemiskinan di Kota Tomohon - Yesita Lestari Bangkang; Agnes L. Ch. P. Lapian; Hanly F. Dj. Siwu (Jurnal Riset Multidisiplin Edukasi, 2025)
Poverty is a condition in which a person or a group of people does not have sufficient resources or access to basic needs to live a decent life. These basic needs include food, clothing, shelter, education, and healthcare. Based on existing theories and several studies that have been conducted, the problem of poverty is generally related to several factors such as the Human Development Index and School Life Expectancy. The purpose of this study is to determine the influence of the Human Development Index and School Duration Expectations on poverty in Tomohon City together. Furthermore, the indirect influence of HDI and School Term Expectations in influencing the poverty level in Tomohon City will also be seen. The data used in this study is secondary data in the form of a time series obtained from the Central Statistics Agency of Tomohon City in 2005-2023. The data was processed using the analysis method multiple linear regression analysis with the help of Eviews 12 program. The results of this study show that HDI has a significant negative effect on poverty in Tomohon City. The Old School Hope has a significant positive effect on poverty in Tomohon City. Simultaneously, HDI and School Old Hope have a significant effect on poverty in Tomohon City